Investigating the Effect of Adding Nano Materials and Carbon Fiber to Impact Strength of Cementitious Composite - Mahdi, Zainab H. (New Approaches in Engineering Research Vol. 9, 2021)
This research involves the addition of nano Silica (NS) with an average particle size of 12nm, micro high reactivity Mitakaaolin (MHRM) particle size \(\ge\) 0.554 \(\le\) 1.271 µm, micro-ground granulated blast-furnace Slag (MGGBFS) particle size \(\ge\) 0.365 <2.932, and Carbon fibers, the length of the fiber 8.5 mm and a diameter of 0.001 mm to cementations mixtures to see their effect on the impact strength and used magnetic water or normal water in mixing blends. The findings showed that cementitious mixtures containing 10% MGGBFS, 10% MHRM, or 2.5 percent NS and reinforced with 2 percent Carbon fibre improved greatly in impact strength, with the absorbed energy to the emergence of the first crack at age 28 days reaching (231.55, 209.49, and 199.49) kN.m, respectively, whereas for the reference cementitious mixtures it has been 1.574 kN.m. The percentage of increase in energy for all various types of magnetic CC with respect to the same nonmagnetic mixtures was a range between 16.6 to 30.92% at first crack and 15.44 to 30.16% at ultimate failure at 28 day.